BULLYING BEHAVIOR IN THE INTEGRATED ISLAMIC BOARDING SCHOOL AT LHOKSEUMAWE CITY - Said Alwi; Saiful Akhyar Lubis; Lahmudin Lubis (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
This study aims to analyze the background, type of behavior of bullying practices and analyze the actions of the Integrated Islamic Boarding School of Lhokseumawe city towards bullying perpetrators. Next, analyze the actions carried out by the Integrated Islamic Boarding School of Lhokseumawe city against bullying victims. The study was conducted in the Integrated Islamic Boarding School of Lhokseumawe City, namely the Integrated Islamic Boarding School of Ulumuddin Uteun Kot Cunda, Misbahul Ulum Paloh, and Darul Ulum Lhok Mon Puteh. This research uses qualitative research with a phenomenological and psychological approach. Data collection techniques were carried out through participant observation, in-depth interviews, and documentation with the data source of the perpetrators of bullying, victims of bullying, and the Ustadz. There are four findings from this study: First; Factors underlying the occurrence of bullying behavior in integrated Islamic Boarding School Ulumuddin, Misbahul Ulum, and Darul Ulum consisted of factors of revenge, family / parenting parents, Islamic Boarding School situation, peer group, and mass media. Second; the forms of bullying that occur are physical bullying which consists of hitting, pushing, throwing, jerking the head, and fighting. Verbal bullying consists of mocking, insulting, calling by nicknames, and berating. Relational bullying consists of opposing, defaming, isolating and alienating. Third; the action taken by the Islamic Boarding School towards the perpetrators of bullying is through the punishment and advice approach, while the psychological approach cannot be implemented optimally due to the unavailability of counseling guidance teachers in the Islamic Boarding School. Fourth, Islamic Boarding School's actions against victims of bullying include coaching and giving advice. Keywords: Bullying behavior of Student, Integrated Islamic Boarding School